1978
DOI: 10.1002/j.1537-2197.1978.tb06149.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Isozymes as Genetic Markers in Citrus

Abstract: The genetic control of isozymes from Citrus and its near relatives was determined for three gene/enzyme systems: glutamate oxaloacetate transaminase, phosphoglucose isomerase and phosphoglucose mutase. These enzymes are controlled by four genes having 19 codominant alleles, 12 of which occur in Citrus subg Citrus. Formal genetic studies were carried out with F, biotypes and F1 populations of known origin. When biotypes were grouped into traditionally recognized species to examine genetic affinities within and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
1
5

Year Published

1980
1980
2012
2012

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(84 citation statements)
references
References 12 publications
7
67
1
5
Order By: Relevance
“…'Ponderosa' was suggested as citron like fruits and notified as monoembryonic with large fruits and hybrid of citron and lemon (Hodgson 1967;Kahn et al, 2001). At the same way, 'Ponderosa' was the most distant cultivar from the other lemons based on leaf isozyme data (Torres et al, 1978). On the other hand, 'Song Panache' lemon have similar-shaped fruit as 'Ponderosa'.…”
Section: Genetic Diversity In Lemon and Relatives (Citron Rough Lemomentioning
confidence: 72%
See 3 more Smart Citations
“…'Ponderosa' was suggested as citron like fruits and notified as monoembryonic with large fruits and hybrid of citron and lemon (Hodgson 1967;Kahn et al, 2001). At the same way, 'Ponderosa' was the most distant cultivar from the other lemons based on leaf isozyme data (Torres et al, 1978). On the other hand, 'Song Panache' lemon have similar-shaped fruit as 'Ponderosa'.…”
Section: Genetic Diversity In Lemon and Relatives (Citron Rough Lemomentioning
confidence: 72%
“…Low level of genetic variation was found among sour oranges (Uzun, 2009). On the other hand, there was no polymorphism in sour oranges based on leaf isozymes (Torres et al, 1978) and SSR markers (Luro et al, 2000). Torres et al (1978) reported that 'Rangpur' lime is quite different morphologically and genotypically from limes and was listed under C. reticulata.…”
Section: Genetic Diversity In Plants 216mentioning
confidence: 99%
See 2 more Smart Citations
“…(1978) consideraram as duas e as três bandas pertencentes a um mesmo loco simples. Soost & Torres (1978) consideraram a hipótese de o gene Got-2 ser um loco duplicado com formação de heterodímero intraloco, que foi considerada não definitiva, porém, seguida por Ballvé et ai. (1991).…”
Section: Methodsunclassified